Eine kurländische Mortarageschichte, nebst Erläuterungen - Katterfeld, Ludwig (Gedruckt bei J.F. Steffenhagen und Sohn, 1883)
Fraktūras burti.
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History; Ebreju vēsture - Latvija; Ebreji - Latvija; Jewish history in Latvia; History of Jews in Latvia; Jews - Latvia - history; Jews in Latvia; Geschichte der Juden in Lettland; Jüdische Geschichte; Juden in Lettland